Pelatihan Manajemen Bisnis dan Digital Branding bagi Pengelola Air Minum dalam Kemasan Asy-Q: Business Management and Digital Branding Strategy Training for Managers of Asy-Q as Bottled Drinking Water Business - Nurfaizana, Della Rulita; Zutiasari, Ika; Fuad, Muhammad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This activity aims to provide knowledge and skills related to business management and digital branding strategy for Asy-Q Bottled Drinking Water (AMDK) managers. The marketing reach of bottled water is not so wide because it is constrained by several things, including marketing. Sales that are still conventional are trying to switch to digital media that is more widely distributed and supported by more attractive product packaging to reach a wider range of consumers. Training with lectures, discussions, practices, mentoring, and evaluation methods was chosen to solve existing problems. The results of the evaluation of the activity showed that the manager as well as the students were able to get to know, create social media, and at the same time market their products. The manager and the Foundation are quite satisfied with the results.